Zip it! - Scaletta, Kurtis (A Topps league story, 2012)
When Pine City Porcupines' batboy Chad breaks an important unofficial rule of baseball: Do not talk to the starting pitcher when he has a perfect game going, the team may lose the game unless Chad can find a baseball card to help break the superstition.